Austrian state policy and its interest in Slovenian folk culture - Rajšp, Vincenc (Traditiones (Ljubljana), 2005)
The article writes about the project "Das Volkslied in Österreich" (Folk Songs in Austria) that was supported by the then Government in Vienna and its meaning for Slovenians. This was the way how Slovenian language was recognisedalso as the language of Slovenian folk culture, after it was into force as an official language and language of education in the time of Maria Theresa
Keywords: Ethnopoetics; ljudske pesmi; slovenska ljudska kultura; slovenščina; Slovene; zgodovinski pregledi; Austria; Avstrija